2005
DOI: 10.1016/j.jvolgeores.2004.09.014
|View full text |Cite
|
Sign up to set email alerts
|

A transient model for explosive and phreatomagmatic eruptions

Abstract: We develop a model for explosive eruptions in cylindrical conduits generated by plug disruption at the top of the conduit. The eruption is calculated for a standard set of parameters for rhyolite. The model takes into account temperature variations and non-Newtonian magma rheology. We analyzed the influence of principal parameters such as fragmentation criteria, magma rheology, and initial conditions. We conclude that the variation of magma temperature is less than 70 K during eruption, and the model with bubb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Relevant problems relate to natural length and time scales, geological setting, confining rock properties and pressures, and interaction under the imposed shear of multiphase magma flowing through dikes. Previous experiments (e.g., Zimanowski et al 1997a, b) identified the magma:water mass ratios that result in different explosion efficiencies under relatively static conditions and for a specific range of scales, but the relationship between magma and water fluxes within the volcanic plumbing and the geohydrological setting of a volcano has yet to be quantified (e.g., Starostin et al 2005). Also unresolved is the effect of dike emplacement on the movement of groundwater.…”
Section: Unsolved Questionsmentioning
confidence: 99%
“…Relevant problems relate to natural length and time scales, geological setting, confining rock properties and pressures, and interaction under the imposed shear of multiphase magma flowing through dikes. Previous experiments (e.g., Zimanowski et al 1997a, b) identified the magma:water mass ratios that result in different explosion efficiencies under relatively static conditions and for a specific range of scales, but the relationship between magma and water fluxes within the volcanic plumbing and the geohydrological setting of a volcano has yet to be quantified (e.g., Starostin et al 2005). Also unresolved is the effect of dike emplacement on the movement of groundwater.…”
Section: Unsolved Questionsmentioning
confidence: 99%
“…Melnik and Sparks (2002a) calculated a temperature profile within the conduit, but as a function of the dissolved water content, rather than an energy conservation equation. Starostin et al (2005), proposed a transient model where they solved also for the energy conservation equation, but considering no crystals in the magmatic mixture, and a single gas phase. In recent years, further models were proposed in the literature (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Discrete volcanic eruptions, in contrast, involve non-steady conditions and are comparatively poorly understood and difficult to model (e.g., Clarke et al, 2002;Dufek and Bergantz, 2005;Starostin et al, 2005). Discrete eruptions imply that volcanic vents are filled by more-orless stagnating debris between eruptive pulses (White, 1991), and this results in eruptive styles different from open-vent conditions.…”
Section: Introductionmentioning
confidence: 99%